Analisis Strategi Pengembangan Potensi Pariwisata Halal Dalam Meningkatkan Industri Kreatif Di Kabupaten Mandailing Natal - Aida Ulviani Nst; Isnaini Harahap; Ria Armayani Hasibuan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the potential of halal tourism in Mandailing Natal Regency, as well as determine the development strategies undertaken to improve the creative industries in Mandailing Natal Regency. The approach taken in this study is descriptive qualitative by using SWOT analysis. Mandailing Natal Regency has a very good tourism potential to be developed. The results of this study based on SWOT analysis show that the strength possessed by halal tourism and creative industries in Mandailing Natal Regency can make it able to survive with various threats. this is because the many attractions that are owned such as strategic location, natural conditions are still beautiful, there are many tourist destinations, culinary and so on so it is clear that the development of halal tourism and creative industries in mandailing natal Regency is in a good position, namely aggressive / developing (so strategy). Where this position in a business has a strong position and the opportunity to grow.. Development of strategies that must be done is the availability of worship facilities throughout the tourist sites so that tourists who visit do not feel kesilitan to perform worship,socialization to the public is needed to continue to maintain environmental cleanliness in accordance with the concept of halal tourism so that tourists who visit feel comfortable, and the last increase promotional activities and marketing of tourist sites.